PEMBERDAYAAN MODERASI BERAGAMA KEPADA MASYARAKAT MELALUI PRAKTIK PEMBIASAAN KHOTMUL QUR’AN DESA RANUGEDANG KEC. TIRIS - Abullies, Mohammad; Musyamil, Ach.; Arifin, Nur (Najah: Journal of Research and Community Service, 2024)
This article delves into the empowerment of religious moderation in the community through the habitual recitation of the Qur'an (Khotmul Qur'an) in Ranugedang Village, Tiris District. In the midst of evolving times, Ranugedang serves as a microcosm facing challenges to foster inclusivity. The initiative not only promotes a balanced understanding of religion but also establishes a robust spiritual foundation. The primary objective is to cultivate a tolerant community, encourage mutual respect, and foster cross-belief cooperation. However, this empowerment encounters challenges such as differing religious views, resistance to change, and the need to address complex social issues.